A fully automatic method yielding initial models from high-resolution cryo-electron microscopy maps. (November 2018) - Terwilliger, Thomas; Adams, Paul; Afonine, Pavel; Sobolev, Oleg
Abstract We report a fully automated procedure for the optimization and interpretation of reconstructions from cryo-electron microscopy (cryo-EM) data, available in Phenix as phenix.map_to_model. We applied our approach to 476 datasets with resolution of 4.5 Å or better, including reconstructions of 47 ribosomes and 32 other protein–RNA complexes. The median fraction of residues in the deposited structures reproduced automatically was 71% for reconstructions determined at resolutions of 3 Å or better and 47% for those at resolutions worse than 3 Å. A fully automated method for modeling protein and protein–RNA complex structure from cryo-EM data, requiring minimal user intervention, is described.